Interrupted versus continuous fascial closure in patients undergoing emergent laparotomy: A randomized controlled trial. Issue 3 (September 2018) - Peponis, Thomas; Bohnen, Jordan D.; Muse, Sandra; Fuentes, Eva; van der Wilden, Gwendolyn M.; Mejaddam, Ali; Alam, Hasan; Kaafarani, Haytham M.A.; Fagenholz, Peter J.; King, David R.; Yeh, D. Dante; Velmahos, George C.; et al.
Abstract : BACKGROUND: The optimal method of fascial closure, interrupted fascial closure (IFC) versus continuous fascial closure (CFC) has never been studied exclusively in the setting of emergency surgery. We hypothesized that IFC decreases postoperative incisional hernia development following emergent laparotomies. METHODS: Between August 2008 and September 2015, patients undergoing emergent laparotomies were consented and randomly assigned to either IFC or CFC. Patients were followed up postoperatively for at least 3 months and assessed for incisional hernia, dehiscence, or wound infection. We excluded those with trauma, elective surgery, mesh in place, primary ventral hernia, previous abdominal surgery within 30 days, or those not expected to survive for more than 48 hours. Our primary endpoint was the incidence of postoperative incisional hernias. RESULTS: One hundred thirty-six patients were randomly assigned to IFC (n = 67) or CFC (n = 69). Baseline characteristics were similar between the groups. No difference was noted in the length of the abdominal incision, or the peak inspiratory pressure after the closure. The median time needed for closure was significantly longer in the IFC group (22 minutes vs. 13 minutes, p < 0.001). Thirty-seven (55.2%) IFC and 41 (59.4%) CFC patients completed their follow-up visits. There was no statistically significant difference in baseline and intraoperative characteristics between those who completed follow-ups and those who did not. The median time from the day of surgery to the day of the last follow-up was similar between IFC and CFC (233 days vs. 216 days, p = 0.67), as were the rates of incisional hernia (13.5% versus 22.0%, p = 0.25), dehiscence (2.7% vs. 2.4%, p = 1.0), and surgical site infection (16.2% vs. 12.2%, p = 0.75). CONCLUSION: There was no statistically detectable difference in postoperative hernia development between those undergoing IFC versus CFC after emergent laparotomies. However, this may be due to the relatively low sample size. LEVEL OF EVIDENCE: Therapeutic/Care Management Study, level III.